Residual strain reduction leads to efficiency and operational stability improvements in flexible perovskite solar cells. Issue 15 (7th July 2022) - He, Sisi; Li, Sibo; Zhang, Anning; Xie, Guanshui; Wang, Xin; Fang, Jun; Qi, Yabing; Qiu, Longbin
Abstract : Efficient and stable flexible perovskite solar cells were fabricated with reduced residual strain by pre-applying strain on the flexible substrate. The flexible cells showed efficiencies of up to 18.7% and operational stability lifetime exceeding 700 h. Abstract : Flexible perovskite solar cells (F-PSCs) hold promise for portable power sources for applications in various fields, such as wearable and portable electronics and lightweight power supply in stratosphere and space applications. To date, it is still a challenge to achieve efficient and stable F-PSCs. Herein, a pre-applied strain on a flexible substrate to release the residual strain of the perovskite layers of the F-PSCs is reported. As a result, the F-PSC based on this strategy yielded a power conversion efficiency (PCE) of up to 18.71%, approaching that of its counterpart based on a glass substrate (20.32%). And it retained 90% of its initial PCE after 300 h under AM 1.5G light illumination with an extrapolated T 80 lifetime (the time over which the device efficiency reduces to 80% of its initial value) exceeding 700 h. Furthermore, the PCE remained above 80% of its initial value even after 1500 tension-only bending cycles. The result of this work paves a possible way toward fabricating efficient and stable F-PSCs.